KEBERHASILAN DAN KEGAGALAN EKSPATRIAT DALAM MEMIMPIN PERUSAHAAN DI INDONESIA: TINJAUAN LITERATUR DAN ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH - Putra, Dian Purnama; Perkasa, Didin Hikmah (LP2M Universitas Bina Bangsa, 2025)
This literature review aims to identify the key factors influencing the success and failure of expatriates in leadership roles within Indonesian companies, focusing on cross-cultural adaptation in the context of International Human Resource Management (IHRM). This study employs a literature review method to analyze the cultural challenges expatriates face in Indonesia, especially regarding high power distance, collectivism, and a preference for indirect communication. Findings indicate that adaptability to these cultural dimensions is crucial for expatriates’ success, particularly in adjusting their leadership style to align with local expectations that emphasize hierarchy and group harmony. Organizational support, such as cultural training, language assistance, and mentoring programs, is considered essential in facilitating this adaptation process. Paternalistic and democratic leadership styles that prioritize employee well-being and involve employee participation have proven effective in building trust within Indonesian teams. The study also highlights the importance of managing cultural stereotypes and biases and the need for reintegration programs to address reverse culture shock when expatriates return to their home countries. By valuing local culture, expatriates can reduce cultural resistance and enhance team collaboration. These findings suggest that expatriate success relies on strong cultural adaptability and adequate organizational support